A Systematic Review and Statistical Analysis of Factors Influencing the Cost-Effectiveness of Transcatheter Aortic Valve Implantation for Symptomatic Severe Aortic Stenosis - Heathcote L; Srivastava T; Sarmah A; Kearns B; Sutton A; Candolfi P (Dove Medical Press, 2023)
Laura Heathcote,1 Tushar Srivastava,1 Archita Sarmah,2 Ben Kearns,1 Anthea Sutton,1 Pascal Candolfi2 1School for Health and Related Research, the University of Sheffield, Sheffield, UK; 2Edwards Lifesciences SA, Nyon, SwitzerlandCorrespondence: Laura Heathcote, School for Health and Related Research (Scharr), the University of Sheffield, Regent Court, 30 Regent Street, Sheffield, S1 4DA., UK, Email l.heathcote@sheffield.ac.ukObjective: Transcatheter aortic valve implantation (TAVI) is a disruptive technology recommended for patients with symptomatic severe aortic stenosis (sSAS). Despite being available for over 15 years in Europe, with an extensive volume of clinical and economic evaluations across all surgical risk groups, there is little evidence on the identification of the key drivers of TAVI's cost-effectiveness. This study sought to identify these factors and quantify their role.Methods: A systematic literature review was conducted to identify published economic evaluations of TAVI. This was supplemented by health technology assessment reports. The primary outcome was the likelihood of TAVI being found cost-effective. Secondary outcomes of TAVI being dominant, and the incremental health benefits of TAVI were also explored.Results: Forty-two studies, reporting 65 unique analyses, were identified. TAVI was found to be cost-effective and dominant in 74% and 20% of analyses, respectively. The latest generation balloon-expandable TAVI device (SAPIEN 3) was more likely to be found cost-effective, as was TAVI use in low-risk populations and when performed via transfemoral access route. There was heterogeneity in the approach taken to economic modelling, which may also influence estimates of cost-effectiveness. Analyses that found TAVI to be dominant always compared it to surgery and usually considered the latest generation balloon-expandable TAVI device. Largest health benefits were observed for the inoperable risk group.Conclusion: For patients with sSAS, TAVI is typically a cost-effective treatment option. There are important differences by device generation, risk group and access route. It is crucial to consider these differences when appraising the health economic evidence-base for TAVI.Keywords: transcatheter aortic valve implantation, cost-effectiveness, severe aortic stenosis, statistical analysis, systematic review